The (Sialyl) Tn antigen: Contributions to immunosuppression in gastrointestinal cancers - Rajesh, Christabelle; Radhakrishnan, Prakash (Frontiers in Oncology, 2023)
Cellular signaling pathways are intricately regulated to maintain homeostasis. During cancer progression, these mechanisms are manipulated to become harmful. O-glycosylation, a crucial post-translational modification, is one such pathway that can lead to multiple isoforms of glycoproteins. The Tn (GalNAc-O-Ser/Thr) and Sialyl Tn (STn; Neu5Ac-GalNAc-O-Ser/Thr) antigens resulting from the incomplete synthesis of fully branched O-glycan chains on proteins contribute to disease progression in the pancreas and other gastrointestinal cancers. The tumor microenvironment (TME) is a major constituent of tumors and a key modulator of their behavior. Multiple cellular and secretory components of the TME dictate the development and metastasis of tumors. Immune cells like macrophages, natural killer (NK) cells, dendritic cells, B and T lymphocytes are a part of the tumor “immune" microenvironment (TIME). The expression of the Tn and STn antigens on tumors has been found to regulate the function of these immune cells and alter their normal antitumor cytotoxic role. This is possible through multiple cell intrinsic and extrinsic signaling pathways, elaborated in this review. Studying the interaction between Tn/STn antigens and the TIME of gastrointestinal cancers can help develop better and more robust therapies that can counteract immunosuppressive mechanisms to sensitize these tumors to anticancer therapies.